Nutritional support for patients sustaining traumatic brain injury: a systematic review and meta-analysis of prospective studies. - Xiang Wang; Yan Dong; Xi Han; Xiang-Qian Qi; Cheng-Guang Huang; Li-Jun Hou (PLoS ONE)
Background In traumatic brain injury (TBI), the appropriate timing and route of feeding, and the efficacy of immune-enhancing formulae have not been well established. We performed this meta-analysis aiming to compare the effects of different nutritional support modalities on clinical outcomes of TBI patients. Methods We systematically searched Pubmed, Embase, and the Cochrane Library until October, 2012. All randomized controlled trials (RCTs) and non-randomized prospective studies (NPSs) that compared the effects of different routes, timings, or formulae of feeding on outcomes in TBI patients were selected. The primary outcomes included mortality and poor outcome. The secondary outcomes included the length of hospital stay, the length of ventilation days, and the rate of infectious or feeding-related complications. Findings 13 RCTs and 3 NPSs were included. The pooled data demonstrated that, compared with delayed feeding, early feeding was associated with a significant reduction in the rate of mortality (relative risk [RR] = 0.35; 95% CI, 0.24-0.50), poor outcome (RR = 0.70; 95% CI, 0.54-0.91), and infectious complications (RR = 0.77; 95% CI, 0.59-0.99). Compared with enteral nutrition, parenteral nutrition showed a slight trend of reduction in the rate of mortality (RR = 0.61; 95% CI, 0.34-1.09), poor outcome (RR = 0.73; 95% CI, 0.51-1.04), and infectious complications (RR = 0.89; 95% CI, 0.66-1.22), whereas without statistical significances. The immune-enhancing formula was associated with a significant reduction in infection rate compared with the standard formula (RR = 0.54; 95% CI, 0.35-0.82). Small-bowel feeding was found to be with a decreasing rate of pneumonia compared with nasogastric feeding (RR = 0.41; 95% CI, 0.22-0.76). Conclusion After TBI, early initiation of nutrition is recommended. It appears that parenteral nutrition is superior to enteral nutrition in improving outcomes. Our results lend support to the use of small-bowel feeding and immune-enhancing formulae in reducing infectious complications.